Motivating Employees to Explore Collaboration Technology in Team Contexts1 - Maruping, Likoebe M.; Magni, Massimo (MIS Quarterly, 2015)
Firms are increasing their investments in collaboration technologies in order to leverage the intellectual resources embedded in their employees. Research on post-adoption use of technology suggests that the true gains from such investments are realized when users explore various system features and attempt to incorporate them into their work practices. However, the literature has been silent about how to promote such behavior when individuals are embedded in team settings, where members’ actions are interdependent. This research develops a multilevel model that theorizes the cross-level influence of team empowerment on individual exploration of collaboration technology. Further, it identifies two cognitions—intention to continue exploring and expectation to continue exploring—that are oriented toward exploring ways to incorporate implemented technology into daily work routines over time. A 12-month field study of 212 employees in 48 organizational work teams was conducted to test the multilevel research model. The results provide support for the hypotheses, with team empowerment having a positive cross-level influence on intention to continue exploring and expectation to continue exploring and these, in turn, mediating the cross-level influence of team empowerment on individual exploration of collaboration technology.